2017
DOI: 10.1187/cbe.16-07-0211
|View full text |Cite
|
Sign up to set email alerts
|

Race and Gender Differences in Undergraduate Research Mentoring Structures and Research Outcomes

Abstract: Undergraduate research with mentorship from faculty may be particularly important for ensuring the persistence of women and minority students in science. This study examines whether undergraduate researchers’ outcomes differ in relation to their gender or race/ethnicity and whether the mentoring structures they experience explain the differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
100
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 84 publications
(144 reference statements)
0
100
1
Order By: Relevance
“…However, we suspect that refinements to the operationalization of mentor network characteristics may produce stronger effects than were shown in the present study. Specifically, recent research has shown unique benefits associated with having peer mentors, as well as being involved in an undergraduate–postgraduate–faculty triadic mentoring relationship [ 49 , 66 , 67 , 115 ]. Therefore, future research on the effects of mentor networks may need to measure specific network structures and the quality of those relationships, rather than mentor network role diversity, as was done in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we suspect that refinements to the operationalization of mentor network characteristics may produce stronger effects than were shown in the present study. Specifically, recent research has shown unique benefits associated with having peer mentors, as well as being involved in an undergraduate–postgraduate–faculty triadic mentoring relationship [ 49 , 66 , 67 , 115 ]. Therefore, future research on the effects of mentor networks may need to measure specific network structures and the quality of those relationships, rather than mentor network role diversity, as was done in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Third, prior tests of the TIMSI prediction linking mentoring to social influence processes and integration operationalized mentoring as the level of support received from a single (typically faculty) mentor. However, advances in mentorship theory have postulated that developing a diversified network of mentors (i.e., diversity in roles [faculty, post baccalaureate, more advanced undergraduate, peer]) can provide mentees with more comprehensive support for their learning and career development [ 15 , 66 72 ]. Mentor network theory suggests individuals benefit from having a diversified network because they are able to rely on the specific strengths of individual mentors serving in a specific supportive role rather than relying on a single mentor providing support across multiple roles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the role of others was evident only while describing how gender identity added to the impostor feelings among women who received disparaging comments from peers and colleagues. Recent research has described the value of forming closed-mentorship networks or triads among undergraduates, new or advanced graduate students/postdocs and faculty members to provide advice, psychosocial support and mentorship (Aikens et al, 2016(Aikens et al, , 2017Chakraverty et al, 2018). As a follow-up to this research, interviews in Phase 2 of the larger study focus on the role of peers, mentors and advisers in perpetuating the impostor phenomenon.…”
Section: Discussionmentioning
confidence: 98%
“…Trainees and laboratory members have requested more supervisory training for their principal investigators (PIs), and in our experience, many faculty agree, especially future and junior faculty (45). However, the responsibilities of research faculty towards their trainees are often shared or passed on to graduate students and postdoctoral scholars, resulting in varied outcomes for different HU groups (44,49,50). In particular, undergraduates have reported negative experiences with graduate students and postdoctoral scholars that involve "scapegoating" and described how these negative relationships "hardened [their] shell" (44).…”
Section: Current Supervisory Practices and Their Impact On The Academmentioning
confidence: 99%